2021
DOI: 10.3390/molecules26092531
|View full text |Cite
|
Sign up to set email alerts
|

Flavones from Combretum quadrangulare Growing in Vietnam and Their Alpha-Glucosidase Inhibitory Activity

Abstract: Combretum quadrangulare Kurz is widely used in folk medicine in Eastern Asia and is associated with various ethnopharmacological properties including hepatoprotective, antipyretic, analgesic, antidysenteric, and anthelmintic activities. Previous phytochemical investigations reported the presence of numerous triterpenes (mostly cycloartanes, ursanes, lupanes, and oleananes) along with dozens of flavonoids. However, the extracts of C. quadrangulare and isolated flavonoids have not been evaluated for their alpha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Ombuin exists in a variety of plants, many of which are used as traditional medicines to treat a variety of human diseases (Dao et al, 2021; Nguyen et al, 2021; Park et al, 1998). At present, the biological activities of ombuin in antibacteria (Dao et al, 2021), anti‐inflammation (Rao et al, 2010), anti‐oxidation (Ranjana et al, 2019), and anticancers (Park et al, 1998) have been reported in previous studies. In a recent study, it was also confirmed that ombuin has the potential to improve type 2 diabetes (Kikiowo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ombuin exists in a variety of plants, many of which are used as traditional medicines to treat a variety of human diseases (Dao et al, 2021; Nguyen et al, 2021; Park et al, 1998). At present, the biological activities of ombuin in antibacteria (Dao et al, 2021), anti‐inflammation (Rao et al, 2010), anti‐oxidation (Ranjana et al, 2019), and anticancers (Park et al, 1998) have been reported in previous studies. In a recent study, it was also confirmed that ombuin has the potential to improve type 2 diabetes (Kikiowo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Ombuin (C 17 H 14 O 7 ) is a natural flavonoid compound that exists in a variety of natural plants and has been proven to have antibacterial (Dao et al, 2021), antioxidant (Ranjana et al, 2019), anticancer (Park et al, 1998), and other biological activities. Rao et al (2010) found that ombuin can significantly and dose-dependently inhibit the release of nitric oxide and cytokines induced by lipopolysaccharide or interferon-γ, and is a potential new anti-inflammatory drug.…”
mentioning
confidence: 99%
“…The α-glucosidase (0.2 U/mL) and substrate (5.0 mM p-nitrophenyl-α-D-glucopyranoside) were dissolved in 100 mM pH 6.9 sodium phosphate buffer [12]. The inhibitor (50 µL) was preincubated with α-glucosidase; then, the substrate (40 µL) was added to the reaction mixture.…”
Section: α-Glucosidase Inhibitory Assaymentioning
confidence: 99%
“…, Psychotria serpens and Siparuna cristata ( Chen 2011 ; Xue et al, 2013 ). Some studies illustrated that jaranol had a potential role in inhibiting SARS-CoV-2 replication ( Leal et al, 2021 ) and exerting anti-cancer ( Woo et al, 2017 ), alpha-glucosidase inhibitory ( Dao et al, 2021 ), anti-bacterial ( Zhang et al, 2019 ), and anti-oxidant activities in vitro ( Quek et al 2021 ). At present, no studies evaluating the effect of jaranol in vivo were found from a PubMed search with the keywords jaranol or kumatakenin.…”
Section: Introductionmentioning
confidence: 99%